Influencing Factors of Outpatients’ Satisfaction in China a Cross-Sectional Study of 16 Public Tertiary Hospitals - Zhou F (Patient Preference and Adherence, 2021)
Fangwei Zhou, Caiming Xu, Yanxiang Sun, Xuehui Meng Humanities and Management School, Zhejiang Chinese Medical University, Hangzhou, Zhejiang Province, People’s Republic of ChinaCorrespondence: Xuehui MengHumanities and Management School of Zhejiang Chinese Medical University, 548# Binwen Road, Binjiang District, Hangzhou, 310051, People’s Republic of ChinaTel/Fax +86 571-86633056Email mengxuehui@aliyun.comPurpose: This study aimed to analyze the status of patient satisfaction in outpatients of tertiary hospitals and the factors affecting patient satisfaction, in order to provide a scientific basis for improving patient satisfaction.Methods: A total of 6480 surveys of outpatients were conducted by a cross-sectional study in 16 tertiary hospitals in the Zhejiang province of China. The main contents of the survey were the basic characteristics of patients. Statistical description, single-factor analysis and binary logistic regression analysis were used to screen influencing factors.Results: Results of this study showed that the total satisfaction score of outpatients was 87.13± 13.47, and higher scored factors in the survey factors were nursing level, the convenience of registration and convenience of appointment diagnosis and treatment. The factors with lower scores were treatment effect, environmental sanitation and comfort and other staffs’ attitudes. Hospital managers should pay attention to the improvement of treatment level, environmental sanitation and comfort and other staffs’ attitudes.Conclusion: In the process of serving outpatients, doctors should pay more attention to patients who are male, 31– 45 years old or over 60 years old, permanent residents, from public institutions, possessed postgraduate education, without medical insurance, and who visiting paediatrics and Chinese medicine hospitals.Keywords: outpatient satisfaction, tertiary hospitals, patient, influencing factor